Toxoplasma gondii: host-parasite interaction and behavior manipulation - da Silva, Rodrigo Costa [UNESP]; Langoni, Hélio [UNESP] (Springer, 2009)
Toxoplasma gondii is an obligate intracellular parasite that causes different lesions in men and other warm-blooded animals. Humoral and cellular immune response of the host against the parasite keeps the protozoan in a latent stage, and clinical disease ensues when immunological response is compromised. Brain parasitism benefits the parasite causing behavioral changes in the host, not only in animals but also in humans. Schizophrenia and epilepsy are two neurological disorders that have recently been reported to affect humans coinfected with T. gondii. Further studies based on host-parasite interaction in several wild or domestic warm-blooded species are still necessary in order to better understand parasitism and behavioral changes caused by T. gondii.